2014
DOI: 10.1002/dmrr.2555
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability and the metabolic syndrome: a systematic review of the literature

Abstract: Heart rate variability is altered differently in men and women with metabolic syndrome. Future studies should follow consistent heart rate variability analysis protocols and metabolic syndrome definitions and include more comprehensive analyses to investigate potential mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 37 publications
7
86
0
1
Order By: Relevance
“…Indeed, the i-IGT group somewhat differed from the other glucose intolerant groups inasmuch as it included a higher number of women and lower number of regular smokers, persons with the metabolic syndrome and those with previous hospitalisation due to myocardial infarction. For example, a recent meta-analysis reported that HRV is reduced in women with the metabolic syndrome compared with those without [42]. Taken together, we cannot rule out the possibility that these differences may have contributed to the relatively low percentage of abnormal HRV measures in the i-IGT group.…”
Section: Discussionmentioning
confidence: 79%
“…Indeed, the i-IGT group somewhat differed from the other glucose intolerant groups inasmuch as it included a higher number of women and lower number of regular smokers, persons with the metabolic syndrome and those with previous hospitalisation due to myocardial infarction. For example, a recent meta-analysis reported that HRV is reduced in women with the metabolic syndrome compared with those without [42]. Taken together, we cannot rule out the possibility that these differences may have contributed to the relatively low percentage of abnormal HRV measures in the i-IGT group.…”
Section: Discussionmentioning
confidence: 79%
“…While MetS is linked to increasing age, there is evidence to suggest that associations with job stress could be more prominent among younger employees [3,23,24]. In addition, there are established gender differences in work stress perception, in occupational trajectories, and in biological stress responses, and distinct analyses of gender would therefore seem appropriate [25,26].…”
Section: Introductionmentioning
confidence: 93%
“…Obesity alters autonomic nervous system (ANS) activity, and HRV generally diminishes with increasing waist circumference (3). The sympathetic nervous system is a key player linking the development and progression of cardiovascular disease with obesity (5).…”
mentioning
confidence: 99%